2017
DOI: 10.1371/journal.pone.0174860
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable poly (lactic acid-co-glycolic acid) scaffolds as carriers for genetically-modified fibroblasts

Abstract: Recent advances in gene delivery into cells allow improved therapeutic effects in gene therapy trials. To increase the bioavailability of applied cells, it is of great interest that transfected cells remain at the application site and systemic spread is minimized. In this study, we tested clinically used biodegradable poly(lactic acid-co-glycolic acid) (PLGA) scaffolds (Vicryl & Ethisorb) as transient carriers for genetically modified cells. To this aim, we used human fibroblasts and examined attachment and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Table 2 presents the main factors evaluated in the articles about to the efficiency of gene transfection and bacterial transformation by different biopolymers and polysaccharides derivates: chitosan [19], dextran [20,21], quaternized cellulose [22] and quaternized chitosan [23]. Other types of substances were used as nonviral vectors such as: plasmid DNA nanostructures with ionic liquid [11], pegylated polyethyleneimine nanoparticles conjugated with folate and galactose [24], cationic liposomes modified with polyallylamine [25], biodegradable polylactic acid-polyethylene glycol-poly (L-lysine) copolymer [26], crotamine [27], poly (oligo-D-arginine) [28], poly (lactic acid-co-glycolic acid) scaffolds [29], polyethyleneimine/pDNA nanocomplexes with anionic hyaluronic acid [30], fourth generation cationic phosphorus (P4) containing dendrimers [31], and monosylated polyethyleneimine [32]. All the materials tested on these studies showed low cytotoxicity and enhanced significantly the efficiency (p < 0.05).…”
Section: Discussion Of Articlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 presents the main factors evaluated in the articles about to the efficiency of gene transfection and bacterial transformation by different biopolymers and polysaccharides derivates: chitosan [19], dextran [20,21], quaternized cellulose [22] and quaternized chitosan [23]. Other types of substances were used as nonviral vectors such as: plasmid DNA nanostructures with ionic liquid [11], pegylated polyethyleneimine nanoparticles conjugated with folate and galactose [24], cationic liposomes modified with polyallylamine [25], biodegradable polylactic acid-polyethylene glycol-poly (L-lysine) copolymer [26], crotamine [27], poly (oligo-D-arginine) [28], poly (lactic acid-co-glycolic acid) scaffolds [29], polyethyleneimine/pDNA nanocomplexes with anionic hyaluronic acid [30], fourth generation cationic phosphorus (P4) containing dendrimers [31], and monosylated polyethyleneimine [32]. All the materials tested on these studies showed low cytotoxicity and enhanced significantly the efficiency (p < 0.05).…”
Section: Discussion Of Articlesmentioning
confidence: 99%
“…Two special types of materials used as vectors for gene transfer were observed: in the study carried out by Togo et al [20], who developed a biodegradable hydrogel composed of 20% w/w dextran aldehyde and 10% w/w ε-poly (L-lysine) (ald-dex/PLL); and in the study carried out by Perisic et al [29], who tested biodegradable poly (lactic acid-co-glycolic acid) (PLGA) scaffolds, clinically used as transient transporters for genetically modified cells. In both studies, a high rate of gene transfection was observed with the use of these materials.…”
Section: Discussionmentioning
confidence: 99%
“…It was observed [10] that poly (DL-lactic acid -co -glycolic acid) (PDLLGA) containing between 0 and 70 % glycolic acid has established amorphous structure, while crystalline copolymer of L-lactic and glycolic acid contains 25 -70 % glycolic acid [10]. Poly(lactic acid -coglycolic acid) has been considered as a suitable material in orthopaedic fixation [22], as tissue engineering scaffolds [23,24], as well as controlled drug delivery systems [25][26][27].…”
Section: Poly(amino Acids)mentioning
confidence: 99%
“…In addition, degradation rate of polymer matrices, corresponding to the rate of tissue restoration, makes the design of new polymer materials for tissue engineering applications a significantly challenging task [23,24].…”
Section: Application Of Biodegradable Polymers In Tissue Engineeringmentioning
confidence: 99%
“…16,17 In vivo, PLGA can be degraded to non-toxic lactic acid and glycolic acid by natural processes, while lactic acid and glycolic acid can be excreted by H 2 O or CO 2 in the excretory system or metabolic pathway. 18 Tissue cells were inoculated onto the biocompatible materials to construct a cellbiomaterial compound, which can form an artificial tissue with corresponding functions, with material degradation and cell proliferation. 19,20 This study was designed to explore a novel technology to construct artificial islet tissue.…”
Section: Introductionmentioning
confidence: 99%